Estimation Model Analysis and Development for Object-Oriented Software Testing - Manchanda, Mahesh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
For practitioners to make informed decisions about resources like time and money, it's crucial that they get an accurate picture of the scale of software projects early in the Software Development Life Cycle (SDLC). The current study proposes an adaption of the standards-based Function Point Analysis (FPA) model to meet the need for a uniform approach for estimating the size of OO software development and testing. At the SDLC's analysis and design stage, when UML diagrams are used, the adapter records the many characteristics of the OO software. During the analysis phase, the size of the development and testing phases is estimated using components derived from the UML use case model. Estimation components are derived from the UML object model and used to calculate the amount of development during the design process..